2022
DOI: 10.3389/fphar.2022.920601
|View full text |Cite
|
Sign up to set email alerts
|

Icariside Ⅱ Attenuates Palmitic Acid-Induced Endothelial Dysfunction Through SRPK1-Akt-eNOS Signaling Pathway

Abstract: Background: Endothelial dysfunction is commonly accompanied by a reduced capacity for nitric oxide (NO) production and decreased NO sensitivity, playing a central role in numerous vascular diseases. Saturated free fatty acids are known to reduce NO production and then induce endothelial dysfunction. Alternative splicing participates in the regulation of cellular and tissular homeostasis and is highly regulated by serine-arginine protein kinase (SRPK1). The role of SRPK1 in the biology of endothelial cells rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…12 Furthermore, research has demonstrated that icariside II has the ability to mitigate endothelial dysfunction induced by PA and to restore cell viability through the SRPK1-Akt-eNOS pathway. 14 In the study, we found that PIAS1 alleviates the ED induced by PA in vitro or by HFD in vivo by activating the PI3K-AKT-eNOS pathway, increasing NO levels, and reducing MDA levels. Studies have shown that the proliferation and migration of endothelial cells play an important role in angiogenesis.…”
Section: Sumoylation and Coupling Of Enosmentioning
confidence: 81%
See 3 more Smart Citations
“…12 Furthermore, research has demonstrated that icariside II has the ability to mitigate endothelial dysfunction induced by PA and to restore cell viability through the SRPK1-Akt-eNOS pathway. 14 In the study, we found that PIAS1 alleviates the ED induced by PA in vitro or by HFD in vivo by activating the PI3K-AKT-eNOS pathway, increasing NO levels, and reducing MDA levels. Studies have shown that the proliferation and migration of endothelial cells play an important role in angiogenesis.…”
Section: Sumoylation and Coupling Of Enosmentioning
confidence: 81%
“…It has been shown that PIAS1 deficiency impairs yolk sac erythropoiesis and vasculogenesis, leading to defective capillary plexus formation and blood vessel occlusions in vivo 12 . Furthermore, research has demonstrated that icariside II has the ability to mitigate endothelial dysfunction induced by PA and to restore cell viability through the SRPK1‐Akt‐eNOS pathway 14 . In the study, we found that PIAS1 alleviates the ED induced by PA in vitro or by HFD in vivo by activating the PI3K‐AKT‐eNOS pathway, increasing NO levels, and reducing MDA levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PA working solution (10 mM) was prepared as described previously. 10 , 11 Briefly, fine-powdered PA (Cat# HY-N0830, MCE, Shanghai, China) was fully dissolved in ethanol, mixed with 10% fatty acid-free bovine serum albumin (Cat# A8850, Solarbio, Beijing, China), co-incubated at 55°C in a water bath, filtered with 0.45-μm membranes, aliquoted into fractions, and stored at −80°C for up to 6 months.…”
Section: Methodsmentioning
confidence: 99%